Creative Thinking And Problem-Solving Abilities : Their Relationship With Psychological Traits Among 10th-GRADE Students In Oman - Alkiyumi, Mohammed Talib Muslem (2010)
The current study sought to investigate the relationship between psychological traits: intrinsic motivation (IM), curiosity (CU), and self-image (SI), and creative thinking abilities: fluency and originality as stated in the Torrance test of creative thinking (TTCT) and two abilities of creative production on problem-solving test: novelty and appropriateness. Kajian yang dijalankan kini lebih tertumpu kepada kajian sama ada trait psikologi terpilih ( motivasi intrinsik, sifat ingin tahu dan imej kendiri ) berkaitan dengan keupayaan pemikiran kreatif kreatif (fluency dan originality) seperti yang terdapat dalam ujian pemikiran kreatif Torrance (TTCT) dan dua keupayaan menyelesaikan masalah (novelty dan appropriateness).